2021
DOI: 10.31234/osf.io/buahk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Examining the robustness of the relationship between metacognitive efficiency and metacognitive bias

Abstract: It is now widely appreciated that confidence ratings are corrupted by metacognitive noise. We recently demonstrated that the level of metacognitive noise increases as the evidence for a decision becomes stronger. This effect leads to the prediction that metacognitive sensitivity and metacognitive bias are confounded such that increasing one’s confidence should result in higher estimated metacognitive sensitivity. In order to test this predicted relationship, we developed a new method to simulate a change in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…An alternative to the normal distribution is a double exponential distribution, which allows for tail asymmetry. In particular, I here consider the Gumbel distribution which has a pronounced right tail, a property that fits recent observations regarding the skewed nature of metacognitive noise (Shekhar and Rahnev, 2021; Xue et al, 2021). Mathematical definitions of all distributions are listed in Appendix 2—table 1.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…An alternative to the normal distribution is a double exponential distribution, which allows for tail asymmetry. In particular, I here consider the Gumbel distribution which has a pronounced right tail, a property that fits recent observations regarding the skewed nature of metacognitive noise (Shekhar and Rahnev, 2021; Xue et al, 2021). Mathematical definitions of all distributions are listed in Appendix 2—table 1.…”
Section: Resultssupporting
confidence: 58%
“…The very same factor (metacognitive noise) that therefore plausibly introduces interindividual differences in metacognitive performance, might obviate a type-1-performance-independent measurement of metacognitive efficiency in this way. Apart from type 1 performance, a recent study has shown that in empirical data the overall level of confidence likewise affects M ratio (Xue et al, 2021) − a confound that may be caused by different levels of metacognitive noise when overall confidence is low or high (Shekhar and Rahnev, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, people undertaking tasks involving trialby-trial ratings of confidence, such as during measurement of local metacognition, can be characterised by their tendency to give high confidence or low confidence ratings in general, termed metacognitive bias. Biases in confidence again need to be accounted for when deriving local metacognitive efficiency parameters -a problem which can be solved via type 2 signal-detection theory (Maniscalco and Lau, 2012, Fleming, 2017, Xue et al, 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, one’s metacognitive bias should be independent of one’s estimated metacognitive ability because metacognitive bias can be manipulated at will (i.e., one can easily increase or decrease their reported level of confidence). However, Shekhar and Rahnev found that higher confidence led to higher Mratio values (the finding was subsequently replicated and extended by Xue et al, 2021). This led them to propose a new model of metacognition with signal-dependent, lognormally-distributed metacognitive noise that could explain this relationship.…”
Section: The Need For Synergy In Research On Measures Models and Neur...mentioning
confidence: 84%
“…An important issue that requires additional research is the fuller characterization of the psychometric properties of Mratio and other measures of metacognitive ability. For example, beyond their dependence on the primary task performance, it is important to empirically assess whether these measures are independent from both response bias and metacognitive bias (the tendency to give either high or low confidence ratings) with recent research suggesting that Mratio may be confounded with metacognitive bias (Shekhar & Rahnev, 2021a; Xue et al, 2021). In addition, fundamental features of these measures such as their test–retest reliability are just beginning to be examined (Guggenmos, 2021).…”
Section: Measures Of Visual Metacognitive Abilitymentioning
confidence: 99%